Alternative replacement heifer investment strategies - Fanning, J.; Marsh, T.; Jones, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effects of beef cow herd inventory management strategies on net income were evaluated in a historical simulation of a representative Kansas beef-cow herd. Constant inventory, counter-cyclical, and dollar-cost averaging strategies were compared to an optimal heifer replacement strategy. Results indicate that price and inventory signals can be used to time replacement heifer acquisition to improve profitability of the average Kansas producer.
Keywords: Beef; Replacement heifer; Market timing; Cattle cycle; Economics